Interaction between universities and business community as a factor of socio-economic development of the region - R. Pashuk, Natalya (2018)
In recent years, the system of higher education in Russia is in a state of dynamic, and not always consistent, transformations. The business sector is faced with the problem of inadequate preparedness level of university graduates, in connection with which employers have to invest additional funds in the professional growth of future employees. Thus, frequent changes in demand in the labor market require universities to organize activities for interacting with the business environment. This paper examines the main problems on the partnership between universities and business community, and also develops a model of effective interaction between higher education institutions and the business sector. The implementation of this model will allow not only to achieve individual results of the activities by the participants of the partnership, but also helps to ensure a synergistic effect that has a positive impact on the development of territories.